A re-description of Discoconchoecia elegans (Sars, 1865) (Ostracoda: Halocyprididae) from high latitudes in the North Atlantic - Stępień, Anna; Błachowiak-Samołyk, Katarzyna; Angel, Martin V. (Zootaxa, 2015)
Discoconchoecia elegans (Sars, 1865) is one of the most frequently recorded species of halocyprid ostracods and specimens are collected in abundance from various latitudes throughout the world oceans. This species is often dominant or subdominant member of the mesopelagic assemblages. However, its body size varies substantially with latitude, posing the question as to whether D. elegans is either a single, highly variable species, or a complex of cryptic and sibling species. Evaluation of the hypothesis that D. elegans is a complex of species requires comparison between the type material and specimens collected from different latitudes. The inadequacy of the original description from the type locality, off the Lofoten Islands (NW Norway), combined with a lack of the type material is preventing critical rating. In this paper Discoconchoecia elegans is redescribed from specimens collected from an area close to Svalbard, using detailed drawings, morphometric measurements of all limbs, and SEM photographs, and it is compared with specimens collected from an area close to the species type locality. The individuals from those two localities show no significant differences, probably because the hydrographic conditions are similar between the two sites.